Coordination between Monetary Policy and Fiscal Policy in Achieving Economic Stability in Iraq during the Period (2005–2024) - Mahmood Akawee, Omar; Raheem Atiyah, Harith (Iraqi Journal for Administrative Sciences, 2026)
This study aims to analyze the impact of coordination between monetary and fiscal policies on achieving economic stability in Iraq using the output gap as an aggregate indicator, based on the ARDL model. The results reveal a long-run equilibrium relationship, with bank credit and public expenditure playing a significant role in reducing the output gap, while inflation exerts a negative and statistically significant effect. In contrast, the interest rate shows a weak and statistically insignificant impact. Public revenues exhibit a positive but insignificant effect due to their reliance on oil revenues and their indirect transmission through public spending. The study concludes that achieving economic stability in Iraq requires strengthening institutional coordination between monetary and fiscal policies, managing liquidity and credit, controlling inflation, and improving the efficiency of public expenditure.